Arcofuzia cana gen. et sp. n. (Insecta, Blattaria, Fuziidae) from the Middle Jurassic sediments of Inner Mongolia, China - Wei, Dandan; Shih, Chungkun; Ren, Dong (Zootaxa, 2012)
Fuziidae is an indigenous Chinese family known from the Middle Jurassic sediments. So far, only three genera have been described from Daohugou locality in Inner Mongolia, China. Arcofuzia cana gen. et sp. n., attributed to the family Fuziidae, is described herein from the Jiulongshan Formation, based on its autapomorphic large body size, distinct forceps-like grasping male cerci, distinct pattern of very wide forewing markings, thick Sc and rich forewing venation with many small but very distinct crossvein-like reticulations.